موقف الفكر الليبرالي في اندونيسيا من القران : دراسة في عوامل نشأته ومظاهر انتشاره = Mawqif al-fikr al-librali fi Indunisiya min al-Qur'an : dirasah fi 'awamil nash'atuh wa-mazahir intisharuh = The attitude of liberalist thought in Indonesia towards the Qur'an: a study of the factors of its rise and the forms of its spread - Solihin, Sohirin Mohammad (International Islamic University Press, 2010)
This article aims at analyzing the position of liberalist thought in Indonesia vis-a-vis the Qur'anic Text and teachings. It examines the attempts of the exponents of this thought at interpretaing the verses of the Qur'an without the least consideration of the rules and methods of interpretation formulated by earlier Muslim scholars. The article also sheds light on the factors that led to the rise and spread of this current of thought and its manifestations and analyzes the views and attitudes of its most prominent advocates.